THE DEPICTION OF JEWISH PEOPLE’S STRUGGLE AGAINST NEGATIVE STEREOTYPES IN ART SPIEGELMAN’S GRAPHIC NOVEL MAUS - Mudita, Nasti (Jurnal Ilmiah Mahasiswa FIB, 2013)
Jewish people have been facing discrimination and negative stereotyping for ages. Conflicts between the majority and Jewish communities, propagated by racial prejudice, result in violent acts committed by the society to isolate the Jews. MAUS is a biography of Art Spiegelman’s father, VladekSpiegelman, which tells about his experience in surviving the persecution of Jewish people in Poland during World War II, and also about Art Spiegelman’s efforts to defy the lingering stereotypes of Jewish people in the present. This research is conducted to analyze the acts of discrimination and negative stereotyping against Jews and the author’s efforts to defy them. Sociological approach is utilized in this research in order to explain the root of prejudice and discrimination against Jewish people, as well as the negative stereotypes labeled to them. The finding of this research shows that VladekSpiegelman, the main character, faced various violent discriminatory acts inflicted against Jews due to the Nazi’s racial propaganda. The propaganda affected the majority by creating an ingroup-outgroup bias, thus forcing the minority Jews into isolation. Nevertheless, VladekSpiegelman survived using cunningness and hard-work ethic; both are stereotypes highly associated with Jews. On the other hand, Art Spiegelman faced difficulties in portraying his father in the graphic novel, since VladekSpiegelman’s aforementioned positive traits becomes negative in the present. The father-and-son conflict brought Art Spiegelman into self-doubting his identity as a Jew. The self-doubt could be diminished by the realization of VladekSpiegelman’s traits as a survivor, thus boosting Art Spiegelman’s pride as part of the Jewish community.   Keywords: prejudice, discrimination, stereotyping, Jews, MAUS, graphic novel.